2021
DOI: 10.1177/11297298211011375
|View full text |Cite
|
Sign up to set email alerts
|

Interventional nephrology and vascular access practice: A perspective from South and Southeast Asia

Abstract: South and Southeast Asia is the most populated, heterogeneous part of the world. The Association of Vascular Access and InTerventionAl Renal physicians (AVATAR Foundation), India, gathered trends on epidemiology and Interventional Nephrology (IN) for this region. The countries were divided as upper-middle- and higher-income countries as Group-1 and lower and lower-middle-income countries as Group-2. Forty-three percent and 70% patients in the Group 1 and 2 countries had unplanned hemodialysis (HD) initiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…In contrast, a nationwide study conducted on 388 nephrologists in India to examine the current vascular access practices among nephrologists found that less than 25% of their ESRD patients started hemodialysis with AVF [ 27 ]. Similarly, in the Philippines, most CKD patients have unplanned initiations of hemodialysis treatment, and only 24% of incident hemodialysis patients start their treatment with AVF [ 9 , 28 ]. Indeed, in Vietnam, a previous study conducted at the same study clinic reported that the rate of AVF creations before hemodialysis initiation was also low at 6.44% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, a nationwide study conducted on 388 nephrologists in India to examine the current vascular access practices among nephrologists found that less than 25% of their ESRD patients started hemodialysis with AVF [ 27 ]. Similarly, in the Philippines, most CKD patients have unplanned initiations of hemodialysis treatment, and only 24% of incident hemodialysis patients start their treatment with AVF [ 9 , 28 ]. Indeed, in Vietnam, a previous study conducted at the same study clinic reported that the rate of AVF creations before hemodialysis initiation was also low at 6.44% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the primary AVF failure rate was 13.13% (13/99, 95%CI: 8.74–21.18%). In the Philippines, the reported primary AVF failure rate was less than 3% [ 9 ]. AVF creations are mainly performed by vascular surgeons, while less than 1% of nephrologists has been involved in interventional procedures including AVF creations [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportions in the prevalent HD patients are 90% for AVF, 8% for non-TCC, and 1% for TCC. The use of an arteriovenous graft is <1% (13). With the advancements in the field of interventional nephrology in recent years, there has been an increasing trend of AVF placement performed by both vascular surgeons and nephrologists, with the goal of reducing the overall number of vascular catheters.…”
Section: Dialysis Accessmentioning
confidence: 99%